Implementation of Crossword Puzzle Learning Media in Indonesian Language Learning at Islamic Elementary School - Putri, Riska Tiara; Rambe, Riris Nurkholidah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this research is to introduce learning media in the form of crossword puzzles at MIN 08 Medan City and assess the impact of this implementation. The qualitative research method was applied, employing a case study approach. The research data is in the form of MIN 08 Medan City applying learning media in the form of Crossword Puzzles. Data collection methods include observation, interviews, and documentation. Data analysis is accomplished by data reduction, data display, and generating conclusions. The findings revealed that MIN 08 in Medan benefited from the use of Crossword Puzzle media in learning Indonesian. This can be seen from the changes that occur in students both when learning is carried out and the results of implementing learning using the media. When learning is in progress, students are more enthusiastic about learning, more focused, and more active in learning. As for the learning outcomes, students who study using Crossword Puzzle media have higher scores than those without using Crossword Puzzle media.